Seismic fragility analysis of steel reinforced concrete frame structures based on different engineering demand parameters. (November 2018) - Xu, Chengxiang; Deng, Jie; Peng, Sheng; Li, Chengyu
Abstract: Nowadays, performance-based seismic design is the focus of earthquake engineering research, in which the seismic performance of a structure is mainly evaluated based on seismic fragility. However, the role of Engineering Demand Parameters (EDPs) on the seismic fragility analysis of Steel Reinforced Concrete (SRC) frame structures remains unclear. This paper presents results on the effects of EDPs on the seismic behavior of a plan-asymmetric SRC building. For this purpose, a nonlinear finite element model of the SRC frame structure was numerically developed using the OpenSees software. This finite element model was then validated using experimental results. The peak interstory drift ratios, as well as the component-based and material-based damage indices, were accordingly employed as EDPs. This study additionally shows seismic fragility curves for an SRC frame structure. The achieved results for the mentioned EDPs were both compared and analyzed. The findings indicated that the EDPs play a role in the seismic fragility analysis for the SRC frame structures. The fragility curves based on a damage index could display the probability of exceeding the ultimate limit states subjected to different seismic intensities, and also showed a similar manner with those based on peak interstory drift ratios. It can be concluded that for an SRC frame structure, the results of seismic fragility analysis using the component-based damage index proved to be more cost-effective and reliable. Highlights: Seismic fragility analysis of SRC structures based on different EDPs is proposed. Results using the component-based damage index are cost-effective and reliable. Results of evaluation based on peak interstory drift ratios is very conservative. Efficacy of the results depends on a damage model employed in analysis process.